2023
DOI: 10.1002/cam4.6453
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of immune checkpoint inhibitors for patients with EGFR‐mutated non‐small cell lung cancer who progressed on EGFR tyrosine‐kinase inhibitor therapy: A systematic review and network meta‐analysis

Abstract: BackgroundNon‐small cell lung cancer (NSCLC) patients harboring epidermal growth factor receptor (EGFR)‐mutated who progressed on EGFR tyrosine‐kinase inhibitor (EGFR‐TKI) therapy have limited therapeutic options. There is still no consensus on the role of immune checkpoint inhibitors (ICIs) in NSCLC with EGFR mutations.MethodsWe did a network meta‐analysis (NMA) with a systematic literature search on PubMed, Embase, Web of Science, and The Cochrane Library. We included all phase II and III randomized controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Our previous NMA showed that ICIs + Chemo + Antiangio was superior to chemotherapy in terms of PFS, OS and ORR for EGFR-mutated NSCLC that progressed after EGFR-TKI, and could be used as the preferred treatment. Even if the ICIs monotherapy, whose OS is better than that of chemotherapy, which can also be used as a treatment option [ 10 ]. In second-line therapy, the CheckMate-078 study showed that Nivolumab significantly prolonged OS and increased ORR compared with chemotherapy [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous NMA showed that ICIs + Chemo + Antiangio was superior to chemotherapy in terms of PFS, OS and ORR for EGFR-mutated NSCLC that progressed after EGFR-TKI, and could be used as the preferred treatment. Even if the ICIs monotherapy, whose OS is better than that of chemotherapy, which can also be used as a treatment option [ 10 ]. In second-line therapy, the CheckMate-078 study showed that Nivolumab significantly prolonged OS and increased ORR compared with chemotherapy [ 11 ].…”
Section: Introductionmentioning
confidence: 99%